1990
DOI: 10.1002/jso.2930440405
|View full text |Cite
|
Sign up to set email alerts
|

Fine needle aspiration biopsy in clinical management of head and neck tumors

Abstract: Ninety-five percent (195) of 203 fine needle aspiration biopsies (FNAB) of head and neck specimens contained adequate tissues for histologic evaluation. No complications or needle tract recurrences were identified. Out of 135 patients whose surgical excision followed FNAB, 5% (7/135) of the biopsies were nondiagnostic. Correlation of cytologic and histologic findings of the remaining 128 FNAB revealed a sensitivity rate of 82% (46/56), a specificity rate of 99% (71/72), and a positive predictive of value of 98… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 9 publications
0
17
0
Order By: Relevance
“…Nondiagnostic and inadequate smears have been reported in 2-10% of cases in the literature [2]; in our cases we observed 5 of 70 (7%) inadequate smears. We excluded these inaccurate results from the statistical analysis the same as several previous studies [8,9,14,15]. In those studies, a test was interpreted just when it was done properly.…”
Section: Discussionmentioning
confidence: 99%
“…Nondiagnostic and inadequate smears have been reported in 2-10% of cases in the literature [2]; in our cases we observed 5 of 70 (7%) inadequate smears. We excluded these inaccurate results from the statistical analysis the same as several previous studies [8,9,14,15]. In those studies, a test was interpreted just when it was done properly.…”
Section: Discussionmentioning
confidence: 99%
“…FNA biopsy is more convenient for the patient and their families, with minimal loss of time from work. 3,19 It also reduces the need to perform excision biopsy in many cases, which often requires time off from work, preoperative blood tests, and radiologic testing. In the pediatric population, FNA helps save children from having to undergo anesthesia and from suffering the complications of excision biopsy.…”
Section: Fna Biopsy For Pediatric Head and Neck Lesionsmentioning
confidence: 99%
“…4,5,7,9 In our study, we showed that ultrasound guidance increased the adequacy (diagnostic yield), sensitivity, and accuracy of neck mass FNC to 94%, 97%, and 96%, respectively. Most strikingly, the accuracy of diagnosing malignant neck masses reached 98% in our study, with a positive predictive value of 98% in 48 malignant cancers, including metastases (P = .023).…”
Section: Discussionmentioning
confidence: 48%
“…3 Therefore, a proper and minimally invasive means of diagnosing a neck mass is crucial for effective treatment planning. Two fine-needle biopsy (FNB) techniques have been widely used in clinical settings with promising diagnostic benefit as outpatient procedures [4][5][6][7] : fine-needle aspiration biopsy (FNA) and fine-needle capillary sampling biopsy (FNC). Of these, FNC, also known as the French biopsy technique, is a type of FNB technique that involves repetitive passes of a 25-gauge needle through the neck mass.…”
mentioning
confidence: 99%